Techniques and methods of creating satirical images in the poetry of Nikolai Oleynikov - Vakhitov Yulai Salavatovich (Periodica Journal, 2024)
The article highlights the artistic and visual features of the poetry of the avant-garde poet Nikolai Oleynikov, in particular parody and “total irony”, erasing the line between creativity and reality.
Keywords: poetry; irony; parody